Genome-wide identification, characterization and expression analysis of the BMP family associated with beak-like teeth in Oplegnathus - Ma, Yuting; Xiao, Yongshuang; Xiao, Zhizhong; Wu, Yanduo; Zhao, Haixia; Gao, Guang; Wu, Lele; Wang, Tao; Zhao, Ning; Li, Jun (Frontiers in Genetics, 2022)
Bone morphogenetic proteins (BMPs), which belong to the transforming growth factor beta (TGF-β) family, are critically involved in the control of developmental processes such as dorsal-ventral axis formation, somite and tooth formation, skeletal development, and limb formation. Despite Oplegnathus having characteri stics of typical beak-like healing teeth and tooth development from discrete to healing, the potential role of BMPs in the development of the beak-like teeth in this group is incompletely understood. In the present study, 19 and 16 BMP genes were found in O. fasciatus and O. punctatus, and they were divided into the BMP2/4/16, BMP5/6/7/8, BMP9/10, BMP12/13/14, BMP3/15 and BMP11 subfamilies. Similar TGFb and TGF_β gene domains and conserved protein motifs were found in the same subfamily; furthermore, 2 common tandem repeat genes (BMP9 and BMP3a-1) were identified in both O. fasciatus and O. punctatus. Selection pressure analysis revealed 13 amino acid sites in the transmembrane region of BMP3, BMP7, and BMP9 proteins of O. fasciatus and O. punctatus, which may be related to the diversity and functional differentiation of genes within the BMP family. The qPCR developmental/temporal expression patterns of BMPs showed a trend of high expression at 30 dph, which exactly corresponds to the ossification period of bones and the beak-like teeth in Oplegnathus. Tissue-specific expression was found for the BMP4 gene, which was upregulated in the epithelial and mesenchymal tissues of the beak-like teeth, suggesting that it also plays a regulatory role in the development of the beak-like teeth in O. punctatus. Our investigation not only provides a scientific basis for comprehensively understanding the BMP gene family, but also helps screen the key genes responsible for beak-like tooth healing in O. punctatus and sheds light on the developmental regulatory mechanism.